1956
DOI: 10.1590/s0373-55241956000100010
|View full text |Cite
|
Sign up to set email alerts
|

Foraminíferos recentes do Brasil: famílias Miliolidae, Peneroplidae e Alveolinellidae

Abstract: Carapaça tão larga quanto longa, paredes lisas e brilhantes; câmaras distintas e suturas suavemente deprimidas. Visto de cima, isto é, do

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2013
2013
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…All tests stained brightly red, which were considered to have been alive when collected (Koukousioura et al, 2011; and references therein), were counted and identified using a stereomicroscope at high magnification. Authoritative keys and texts utilized included: Tinoco (1955Tinoco ( , 1958, Narchi (1956), Barker (1960), Closs and Barberena (1960), Bock et al (1971), Almasi (1978), Boltovskoy et al (1980), Machado (1981), Leipnitz (1991), Leipnitz et al (1992), Levy et al (1995), Andrade (1997) and Rossi (1999). Selected specimens of small, difficult to identify species, were coated with Au/Pd 200Å pellicle and photomicrographs were obtained using a scanning electron microscope (Zeiss DSM 940A).…”
Section: Samplingmentioning
confidence: 99%
“…All tests stained brightly red, which were considered to have been alive when collected (Koukousioura et al, 2011; and references therein), were counted and identified using a stereomicroscope at high magnification. Authoritative keys and texts utilized included: Tinoco (1955Tinoco ( , 1958, Narchi (1956), Barker (1960), Closs and Barberena (1960), Bock et al (1971), Almasi (1978), Boltovskoy et al (1980), Machado (1981), Leipnitz (1991), Leipnitz et al (1992), Levy et al (1995), Andrade (1997) and Rossi (1999). Selected specimens of small, difficult to identify species, were coated with Au/Pd 200Å pellicle and photomicrographs were obtained using a scanning electron microscope (Zeiss DSM 940A).…”
Section: Samplingmentioning
confidence: 99%
“…Os foraminíferos bentônicos recentes de mar profundo na margem continental brasileira têm sido pouco estudados. Segundo Narchi (1956) (NARCHI, 1956).…”
Section: Foraminíferos Da Margem Continental Sul-sudeste Brasileiraunclassified